New explicit approximate solution of the Boltzmann equation in the case of the hard sphere model - Hukalov, O.; Gordevskyy, V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 We construct an approximate solution to the nonlinear kinetic Boltzmann equation for the case of hard-sphere model. It has the form of an infinite sum of some Maxwellian modes with coefficient functions of the spatial coordinate and time. We establish sufficient conditions for the coefficient functions and hydrodynamic parameters appearing in the distribution and allowing us to make the analyzed deviation arbitrarily small.